2013
DOI: 10.1038/cddis.2013.191
|View full text |Cite
|
Sign up to set email alerts
|

Gossypol and an HMT G9a inhibitor act in synergy to induce cell death in pancreatic cancer cells

Abstract: The histone methyltransferase G9a is overexpressed in a variety of cancer types, including pancreatic adenocarcinoma, and promotes tumor invasiveness and metastasis. We recently reported the discovery of BRD4770, a small-molecule inhibitor of G9a that induces senescence in PANC-1 cells. We observed that the cytotoxic effects of BRD4770 were dependent on genetic background, with cell lines lacking functional p53 being relatively resistant to compound treatment. To understand the mechanism of genetic selectivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 41 publications
3
72
0
Order By: Relevance
“…In a study, it has been reported that BRD4770 lead to reduction of cancer proliferation in PANC-1 cell lines. Indeed this study confirmed that BRD4770 has anti-inhibitory effect on histone methyltransferase G9, an enzyme with high expression in cancer types [23]. A number of DNA methylation inhibitors are under study including azacitidine, decitabine and hydralazine.…”
Section: Cancer Treatment By Epigenetic Interferencesupporting
confidence: 77%
“…In a study, it has been reported that BRD4770 lead to reduction of cancer proliferation in PANC-1 cell lines. Indeed this study confirmed that BRD4770 has anti-inhibitory effect on histone methyltransferase G9, an enzyme with high expression in cancer types [23]. A number of DNA methylation inhibitors are under study including azacitidine, decitabine and hydralazine.…”
Section: Cancer Treatment By Epigenetic Interferencesupporting
confidence: 77%
“…Also, when TP53-mutant PANC-1 cancer cells are cotreated with the autophagy inducer gossypol, autophagy and even autophagy-related cell death are enhanced. 56 In summary, the EHMT2-mediated methylation level of H3K9 acts as a repressor of autophagy under normal conditions. However, after autophagy induction EHMT2 is readily removed from promoters of autophagyrelated genes leading to disappearance of H3K9me2, increase in H3K9ac and thus transcription of genes.…”
Section: H3k9me2mentioning
confidence: 97%
“…12 Others and we have shown that antagonizing the survival marks during autophagy can indeed induce cell death. 37,56 Both removal of the HMT EHMT2 by the specific chemical inhibitor BRD4770, decreasing the level of the repressive H3K9me2 histone modification, or increase of the active H4K16ac histone modification (through overexpression of KAT8, or antagonizing SIRT1 using valproic acid, Ex527 or siRNA) during autophagy, result in cancer cell death. Inhibition of EHMT2 or induction of H4K16ac both lead to a more open chromatin structure eliminating the tight control of autophagy-related gene expression potentially resulting in an autophagic overstimulation and finally cell death.…”
Section: H3k9me2mentioning
confidence: 99%
“…In efforts to continue developing additional and even more selective compounds to target specific epigenetic pathways, the most contemporary SAM-competitive inhibitor BRD4770 was discovered to selectively inhibit G9a and induce senescence in pancreatic adenocarcinoma cells [30]. Furthermore, when combined with the natural product gossypol, BRD4770 displays enhanced cytotoxicity and is suggested to work in a synergistic manner with gossypol to induce autophagy-related cell death in p53-mutant cells [31]. Thus, these novel combinatorial drug treatments may have promise as epigenetic therapies to combat cancer progression.…”
Section: Pharmacological Targeting Of the Hp1-hmt Pathwaysmentioning
confidence: 99%